Application of Games-Based Memorization Models in Improving Students' Critical Thinking Skills in Learning Social Studies - Tetep; Alni Dahlena (Research and Innovation in Social Science Education Journal (RISSEJ), 2024)
The low interest of students in social studies subjects is possible because the teacher's efforts have not been optimal to increase the creative thinking of students' learning. Students' critical thinking skills are still low, seen during the current learning process, students are not encouraged to improve their thinking skills. The purpose of this study was to identify an increase in students' critical thinking skills after applying the games-based learning model of memorization. Study This using quantitative methods, this type of research uses quasy experiments, the sample in this study were class VII students at SMPN 1 Tarogong Kidul, the instrument Which used For ability critical thinking is pretest and posttest, observation and documentation study. Based on research results and data management using the Mann Whitney test obtained Sig.0.021 and α = 0.05 means Sig. <α, then the game-based memorization learning model can improve students' critical thinking skills. So that students have the skills and abilities to think critically in the social studies learning process.